The Role Of Education Financing In The Development Of Infrastructure And Learning Facilities At Mts Hidayatul Falah Nagrak, Sukabumi Regency - Hariyanto, Teguh; Tamlekha, Tamlekha; Fasya, Nizar Muhammad; Badrudin, Badrudin; Zakiyah, Qiqi Yuliati (UNIVERSITAS PAKUAN, 2025)
This article examines the role of education financing in the development of infrastructure and learning facilities at MTs Hidayatul Falah in Nagrak District, Sukabumi. Using a case study approach with a descriptive qualitative method, data was collected through in-depth interviews, field observations, and document analysis. The findings highlight that education financing, particularly through the BOS (School Operational Assistance) funds, community contributions, and alumni donations, significantly contributes to the construction of classrooms, computer labs, libraries, and other essential facilities. However, the study also identifies major challenges, including funding limitations, low community participation, and administrative constraints. Efficient and transparent financial management, along with collaboration among stakeholders, can optimize education financing to enhance the quality of educational infrastructure. This research offers practical insights for private educational institutions in rural areas to develop sustainable and accountable financing strategies.